Effects of Shochu Distillery By-products on the Energy Budget of Common Carp - Mokolensang, Jeffrie Fredrik; Manu, Lusia; Manu, Gaspar D. (Sam Ratulangi University, 2023)
The effects of Shochu distillery by-products (SDBP) were investigated by supplementary different level of SDBP to the basal diets for Japanese Common carp. To clarify the growth performances, energy budget equation was applied in this study. The feeding trial was conducted for 20 days by feeding the test diets containing SDBP at 0, 2,1 and 4.2%, respectively. Based on the energy budget equation, the digestible energy (DE) requirements for the maximum growth ranged from 49.0 – 55.8 kcal/ind/d. The 4.2% SDBP diet yielded 6.5% higher growth energy but 7.1% lesser metabolic energy than the control. The energy budget on 4.2% SDBP diet accounted for 10.6% of feces (2.42 kcal/ind/d), 4.2% of non-fecal (0.93 kcal/ind/d), 39.4% of metabolic loss (9.03 kcal/ind/d) and 45.9% of growth (10.5 kcal/ind/d), respectively. Correspond to the control, non-fecal and metabolic energies were lower, in 4.2% SDBP resulting in the higher product energy. The above results indicate that SDBP can be utilized as a supplement ingredient for the growth promotion of carp feed, since it could provide a superior property for growth energy of fish by reduced energy of metabolic loss and non-fecal losses. Key words: Shochu distillery by-products; Energy requirements; Metabolic loss; Growth; Carp